2015
DOI: 10.1016/j.atherosclerosis.2015.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis following renal injury is ameliorated by pioglitazone and losartan via macrophage phenotype

Abstract: Objective-Chronic kidney disease (CKD) amplifies atherosclerosis, which involves reninangiotensin system (RAS) regulation of macrophages. RAS influences peroxisome proliferatoractivated receptor-γ (PPARγ), a modulator of atherogenic functions of macrophages, however, little is known about its effects in CKD. We examined the impact of combined therapy with a PPARγ agonist and angiotensin receptor blocker on atherogenesis in a murine uninephrectomy model.Methods-Apolipoprotein E knockout mice underwent uninephre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…PPARγ agonists ameliorate diabetic atherosclerosis not only through beneficial effects on glucose and lipid metabolism, but also through anti‐inflammatory and immunoregulatory activities. PIO has been shown to improve the imbalance of regulatory and effector T cells in a uremic murine model , to regulate macrophage phenotype in a renal‐injury murine model , to reduce plaque inflammation in a non‐diabetic ApoE −/− mice model and to reduce the proportion of M1 monocytes/macrophages with consequent improvement in circulatory M1/M2 imbalance in obese type 2 diabetic patients . Consistently, in the present study, PIO administration significantly decreased the higher proportion of peripheral M1 monocytes/macrophages and improved the M1/M2 imbalance in diabetic circumferences.…”
Section: Discussionsupporting
confidence: 88%
“…PPARγ agonists ameliorate diabetic atherosclerosis not only through beneficial effects on glucose and lipid metabolism, but also through anti‐inflammatory and immunoregulatory activities. PIO has been shown to improve the imbalance of regulatory and effector T cells in a uremic murine model , to regulate macrophage phenotype in a renal‐injury murine model , to reduce plaque inflammation in a non‐diabetic ApoE −/− mice model and to reduce the proportion of M1 monocytes/macrophages with consequent improvement in circulatory M1/M2 imbalance in obese type 2 diabetic patients . Consistently, in the present study, PIO administration significantly decreased the higher proportion of peripheral M1 monocytes/macrophages and improved the M1/M2 imbalance in diabetic circumferences.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction of atherosclerosis by 10,12 CLA supplementation was also striking, given the increased macrophage content of those lesions. It has been previously reported that atherosclerosis regression in response to thiazolidinedione treatment occurs despite increased lesion macrophage content [ 34 ], which were identified as largely resident M2 macrophages. Moreover, it is becoming increasingly appreciated that M2 macrophages support lesion regression by resolving inflammation and promoting tissue remodeling [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that atherosclerosis regression in response to thiazolidinedione treatment occurs despite increased lesion macrophage content [ 34 ], which were identified as largely resident M2 macrophages. Moreover, it is becoming increasingly appreciated that M2 macrophages support lesion regression by resolving inflammation and promoting tissue remodeling [ 34 , 35 , 36 ]. Mice deficient in transcription factors that are required for M2 polarization have accelerated atherosclerosis [ 37 ], while administering type-2 cytokines such as IL-4 to mice protects against atherosclerosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…TZDs also promote M2 macrophages in other disease states. Pioglitazone enhanced M2 polarization in atherosclerotic lesions, diet-induced obesity, and a model of insulin resistance [ 77 79 ]. Rosiglitazone likewise enhanced expression of Arg-1 and CD206 in peritoneal and adipose tissue macrophages and in an in vitro model of COPD [ 80 82 ].…”
Section: Ppar γ and Alternative Macrophage mentioning
confidence: 99%